Interaction dynamics of multiple ecosystem services and abrupt changes of landscape patterns linked with watershed ecosystem regime shifts. (June 2023) - Zhao, Junyan; Li, Jiajia; Zuo, Lingli; Liu, Guohua; Su, Xukun
Graphical abstract: Highlights: The interaction dynamics of multiple ecosystem services have strong link with watershed ecosystem regime shift. The water yield and the grain production are core ecosystem services which can define ecosystem states. The abrupt functional changes had 1-year lag with the structural changes. Watershed ecosystem can occur as alternative stable states. Abstract: Functional and structural regime shifts have been observed among many ecosystems. Understanding regime shifts in watershed ecosystems is crucial for landscape management and sustainable development. We propose the perspective that the relationship dynamics of ecosystem services (ESs) can reflect watershed ecosystem regime shifts. An assessment of the critical transitions in watershed landscape patterns is integrated to support the regime shift analysis. The downstream basin of the Nu-Salween River (NSR) was selected as the study area to demonstrate regime shifts occurring from 1999 to 2019. To detect the functional critical transition, changes in the relationships among various ESs, including in the habitat quality for biodiversity (HQ), carbon storage (CS), water yield (WY), soil conservation (SC) and grain production (GP), were revealed using time series correlation analysis. To identify the critical structural transitions of watershed, the Pettitt test and principal component analysis (PCA) were used to display changes in landscape patterns. The results showed that (1) WY and GP were key ESs that could define watershed stable states; (2) three states, the "coordinated state" from 1999 to 2008, the "transient state" from 2009 to 2013 and the "trade-off state" from 2014 to 2019, were identified in the downstream basin of the NSR; and (3) the watershed functional critical transition had a 1-year time lag with the structural critical transition. This research revealed the nonlinear dynamics of a complex system in watersheds, and the detection of regime shifts that integrate the interaction dynamics of ESs can better serve watershed management to cope with abrupt changes.